Philadelphia chromosome-positive acute lymphoblastic leukemia in children: new and emerging treatment options. Issue 6 (December 2010) - Schultz, Kirk R; Prestidge, Tim; Camitta, Bruce
Philadelphia chromosome-positive (Ph + ) acute lymphoblastic leukemia (ALL) in children and adolescents has, until recently, been considered one of the poorest-risk subgroups of ALL. With chemotherapy alone, only 20–30% of children with Ph + ALL are cured. Allogeneic hematopoietic cell transplantation in first complete remission cures 60% of patients with a closely matched donor. Although targeted tyrosine kinase inhibitors (TKIs) have limited activity against Ph + ALL as a single agent, they have been evaluated in combination with chemotherapy with promising results. The early results of Children's Oncology Group trial AALL0031 have shown 88% 3-year event-free survival for Ph + patients treated with intensive chemotherapy plus continuous-dosing imatinib. This suggests that chemotherapy plus TKIs may be the initial treatment of choice for Ph + ALL in children. However, the numbers are small in this trial and confirmatory results are not yet available from the European Intergroup Study on Post Induction Treatment of Philadelphia Positive Acute Lymphoblastic Leukaemia with Imatinib trial. Additional issues include determining the most effective TKI (imatinib, dasatinib or nilotinib) and the most effective, least toxic chemotherapy backbone. The experience of adding a targeted agent such as a TKI to the standard chemotherapy regimen suggests that this strategy might be applied to other ALL subtypes to achieve both increased efficacy and decreased toxicity.